Digitalität in der Theaterwissenschaft. Forum der AG ARCHIV mit NFDI4Culture - Ertel, Erhart; Lamb, Jochen; Münzmay, Andreas; Primavesi, Patrick; Probst, Nora; Rittershaus, David; Schäfer, Martin Jörg; Voß, Franziska (Matters of Urgency – Herausforderungen der Gegenwart in Theater und Wissenschaft)

Geschichte und Umwelt von Rechenzentren; Rezension zu: Dommann, Monika; Rickli, Hannes; Stadler, Max (Hrsg.): Data Centers. Edges of a Wired Nation, Zürich 2020; Gugerli, David; Wichum, Ricky: An den Grenzen der Berechenbarkeit. Supercomputing in Stuttgart, Zürich 2021 - Schmitt, Martin (HSozKult)
Keywords: Rechenzentren; Geschichte; Umweltgeschichte; Nachhaltigkeit; Supercomputing; Technikgeschichte

Beethovens Eigenbearbeitungen und digitale Heuristik. Erkundungen mit den synoptischen Doppeleditionen und Analysewerkzeugen des Projekts Beethovens Werkstatt - Münzmay, Andreas

Vernetzte Musikquellen des 19. Jahrhunderts. Überlegungen zum Zusammenspiel wissenschaftlicher Editionen mit RISM am Beispiel des Stuttgarter Faust 1832 - Frömmel, Lena; Münzmay, Andreas (Musikquellen des 19. Jahrhunderts in Deutschland. Herausforderungen und Chancen)
This article explores the challenges and opportunities of documenting and cataloguing 19th-century music sources in Germany, using the 1832 Stuttgart production of Goethe’s Faust with music by Peter Joseph von Lindpaintner as a case study. The main focus lies on the potential interplay between (digital) critical music editions and RISM as complementary approaches to source documentation. While RISM has traditionally concentrated on pre-1800 sources, the vast and complex landscape of 19th-century music-theatrical materials—especially handwritten performance materials, but also printed sources—calls for new collaborative strategies. Drawing on the Faust edition within the OPEN Edirom project, which publishes data in open, structured formats (TEI and MEI) and makes them accessible via the RADAR4Culture repository and the Culture Knowledge Graph, the article argues for closer integration between editorial projects and RISM through stable identifiers and Linked Open Data principles. Editorial descriptions do not compete with RISM records but meaningfully extend them, and vice versa. The case study illustrates how editorial source descriptions and full-text editions could enhance the informational scope and augment the reach of RISM, and how RISM could serve as a basis for more granular, interconnected, and FAIR-compliant musicological research infrastructures. The article proposes RISM as a central access point for distributed research data and outlines the simple yet effective steps researchers can take to enhance discoverability and interoperability: namely, by using (or if necessary, creating) RISM IDs and by publishing data with persistent Digital Object Identifiers (DOIs).

Peter Joseph von Lindpaintner, Ouverture, Entreacte, Chöre und Lieder zu Goethes Faust nach der szenischen Einrichtung von Carl Seydelmann (1832)
The present OPEN Edirom digital edition of Goethe’s Faust presents the literary and musical text of the work as it was possibly performed at its premiere (Friday, March 2, 1832) and consecutive performances under the direction and participation of Carl Seydelmann (directing the production and playing the role of Mephistopheles) and Peter Joseph von Lindpainter in the Stuttgart Hoftheater in 1832 (March 11, May 28, October 12) and 1833 (May 14, December 27), in accordance with the surviving sources, i.e., the original theatre material preserved in the Württemberg State Library in Stuttgart (D-Sl). This material constitutes a nearly complete autograph source package consisting of text adaptation (an autograph by Seydelmann incorporated into a copy of the print edition published by Cotta in Tübingen in 1830) and corresponding music (two volumes with autograph scores by Lindpaintner).

Digitalisierung und Umwelt – eine verflochtene Digitalgeschichte der Gegenwart im Angesicht des Klimawandels - Schmitt, Martin
Keywords: Digitalisierung; Digitalgeschichte; Umweltgeschichte; Anthropozän; Computer; Rechenzentrum; Digital History

Die Vorgeschichte der „sozialen Medien“. Über die Träume digitaler Vergemeinschaftung und freier Kommunikation - Schmitt, Martin (Soziale Medien – wie sie wurden, was sie sind)
Sind „soziale Medien“ überhaupt ein Thema für die Geschichtswissenschaft? Ja, denn die längere Geschichte der Digitalisierung, in der die „sozialen Medien“ einzuordnen sind, zählt bereits über 80 Jahre. Konrad Zuse und andere Ingenieure entwickelten seit 1941 die ersten Digitalcomputer, Unternehmer*innen, Wissenschaftler*innen und Staatenlenker*innen setzten diese seit den 1950er Jahren für ihre Zwecke ein, die Zivilgesellschaft adaptierte sie in den darauffolgenden Dekaden – all das prägte die sozio-digitale Landschaft der späteren „sozialen Medien“. Als unmittelbar „nach dem Boom“ etwa um 1970 zahlreiche Industriegesellschaften einen strukturellen Wandel in Wirtschaft, Gesellschaft und Politik durchlebten, war eine Antwort darauf die vermehrte Digitalisierung und Vernetzung. Daraus entwickelte sich die 1990er Jahre als markante Dekade von World Wide Web, Google und Chatdiensten. Die Entwicklung der „sozialen Medien“ ist also unter anderem in eine ökonomische und gesellschaftliche Entwicklung der Aufmerksamkeitsökonomie und in die längeren Veränderungen von Wirtschafts- und Gesellschaftsordnungen der Ausdifferenzierung und partiellen Individualisierung seit den 1960er Jahren einzuordnen. Dadurch lässt sich besser verstehen, welche Prämissen ihnen zugrunde lagen, welche Möglichkeitsräume und Probleme sich daraus ergaben und warum sie die heutige Öffentlichkeit in einer bestimmten Art und Weise dominieren – ohne sie jedoch zu determinieren.
Keywords: Digitalgeschichte; Soziale Medien; Technikgeschichte; World Wide Web; Digitalisierung

Open Edirom: From hybrid music edition to open data publication - Frömmel, Lena; Bachmann, Tobias; Plaksin, Anna Viktoria Katrin; Münzmay, Andreas (Proceedings of the 11th International Conference on Digital Libraries for Musicology)
The OPEN Edirom project is developing a digital edition of incidental music for Goethe’s play Faust, representing an innovative initiative within the realm of music philology and MEI/TEI edition. Embracing the "data first" principle, OPEN Edirom prioritizes making its content openly accessible, thereby enabling diverse potential uses for researchers and performers. Our aim involves presenting the scholarly text and music edition in its entirety, incorporating its various forms of data, i.e. music, texts, source images, metadata, and annotations, all displayed with Edirom software. The piece we edit in this project is Goethe’s renowned play Faust I, as adapted by Carl Seydelmann, along with the corresponding music composed by Peter Joseph von Lindpaintner for the Court Theatre in Stuttgart. The work premiered in 1832. This paper delves into the concept of music edition as open data publication and delineates its advantages over analog and hybrid editions in terms of reusability and alignment with the FAIR principles. It also addresses the challenges encountered in data preparation, both specific to incidental music and in general data processing. Furthermore, we propose solutions and recommendations for similar projects based on our insights.

Digitale Interpretationsedition und Filmmusikedition als multimodale Schwestern – Gemeinsame Herausforderungen und Lösungsansätze - Berndt, Axel; Münzmay, Andreas

Multi-Modal Data Networks in Music: Thoughts on a Digital Performance Edition - Berndt, Axel; Münzmay, Andreas; Bömcke-Vollmer, Frithjof (DAGA 2024 – 50. Jahrestagung für Akustik)

Multi-Modal Data Networks in Music: Thoughts on a Digital Performance Edition and its Potential for Ethnomusicology - Berndt, Axel; Bömcke-Vollmer, Frithjof; Münzmay, Andreas ({Diskografentag: International Conference on Recorded Music})

Socialist AI? Societal Use, Economic Implementation, and the Tensions of Applied Computer Science in Late Socialist GDR - Schmitt, Martin (IEEE Annals of the History of Computing)
Keywords: Sozialismus; Schachcomputer; Deutschland {<}DDR{>}; KI; Schach; Spätsozialismus; 1980er-Jahre

Open Data in musikphilologischen Projekten: Herausforderungen, Strategien, Potenziale - Kepper, Johannes; Münzmay, Andreas (DHd2023: Open Humanities, Open Culture)

Banking the Future of Banking: Savings banks and the Digital Age in East and West Germany - Schmitt, Martin (Prophets of Computing: Visions of Society Transformed by Computing)
Keywords: Sparkassen; Computer; 1960er; Kreditwirtschaft; Digitalisierung; Deutschland {<}DDR{>}; Deutschland {<}Bundesrepublik{>}

Du Châtelet and Kant: Claiming the Renewal of Philosophy - Hagengruber, Ruth Edith (Époque Émilienne Philosophy and Science in the Age of Émilie Du Châtelet (1706-1749))
n 1789, Eberhard repudiated Kant’s claim expressed in the first edition of his Critique of Pure Reason to have delivered a new, namely transcendental turn in philosophy, as he was able to retrace our cognition to the origin of phenomena instead of delivering a “merely logical deduction”. Eberhard holds that there was nothing new, but all delivered in Leibniz and Wolff; to prove his claim he refers to a quote from Du Châtelet, taken from a paragraph where she determines the right understanding as to be able “to penetrate to the origin of phenomena”. This paper brings Du Châtelet into discourse with Kant via this Eberhard quote. In its first part, it investigates the use of her quote in the Kant-Eberhard controversy. The second part serves to ground the quote in Du Châtelet’s epistemology. It lays out how to understand Du Châtelet’s claim to penetrate to the origin of phenomena. Du Châtelet’s claim to have renewed philosophy must be taken seriously, and it is helpful for rethinking the German philosophical development from the rationalists to Kant through including Du Châtelet’s theory of cognition.
Keywords: Émilie Du Châtelet; History of Science; Newton; Kant; Eberhard; Wolff; Leibniz

Du Châtelet, Émilie (1706–1749) - Hagengruber, Ruth (Encyclopedia of Early Modern Philosophy and the Sciences)
Of the many outstanding female philosophers of the European Enlightenment, Emilie Du Châtelet excelled as a physicist, a philosopher, and a mathematician, as well as a Bible critic. She was famous in her lifetime and was not completely forgotten thereafter. Among her admirers, correspondents and friends were the most acknowledged scholars of her time, including Voltaire, Clairault, Maupertuis, Diderot, Helvetius, La Mettrie, Buffon, Christian Wolff, Leonard Euler, and Johann II Bernoulli. Her philosophical work enjoyed high reputation and her opus magnum, the Institutions physiques, was translated into Italian and German and proved her to be an intellectual of European stature. Its defense of living forces and its implied forecast into dynamics as well as her methodological grounding of scientific knowledge as hypothetical, impacted philosophy and science. Reality must by nature escape us. What we perceive are phenomena. Du Châtelet explains the function of space and time to trace us back to the origin of phenomena. Her influence on Kant is evident. Next to her writings in physics, mathematics, philosophy, language, and logic, she contributed to morality and ethics. Du Châtelet left an opus of quite systematic breadth. This impressive publishing activity excels in the amount of its scientific and philosophical production to which a vast collection of manuscripts must be added.She argued against prejudice and idolatry in philosophy and science. Science is a cooperative undertaking over history and beyond nations. Her moral writings align with ideas of the French materialists. Du Châtelet translated and commented on Newton’s Principia, preparing thus the fertile soil of the generation of physicists to come in France.
Keywords: aura Bassi Luise Gottsched Immanuel Kant Dourtous de Mairan Johann II Bernoulli Algarotti Buffon d’Alembert La Mettrie Principle of contradiction Hypotheses Enlightenment Leibniz-Clarke Correspondence Living forces Dead forces; happiness Space Imaginary beings Monads Epicurus Ethics Women philosophers Newton’s laws Principia Motion inertia Active force Vis viva Vis mortua Hypothetic reasoning Hypotheses; a priori principles; Experience; Dead forces; Living forces; Energy Dynamics

Women in Early Modern Philosophy and Science: An Introduction - Hagengruber, Ruth Edith (Encyclopedia of Early Modern Philosophy and the Sciences)
Essential ideas significantly connected to humanism, Renaissance, and early modern philosophy stem from women’s pens. The supportive role of women in the early modern period has hardly been recognized up to today. The relevant issues women have contributed to range from commentaries on and critiques of the Bible, and their demands for equality and the critique of political institutions, topics that became eminent enhancers of political and societal change in the relevant period of early modern philosophy, to enlightenment philosophy.

Brückenschläge zwischen Musikwissenschaft und Informatik. Theoretische und praktische Aspekte der Kooperation

Brückenschläge zwischen Musikwissenschaft und Informatik – Vorbemerkung - Münzmay, Andreas; Aquavella-Rauch, Stefanie; Veit, Joachim (Brückenschläge zwischen Musikwissenschaft und Informatik. Theoretische und praktische Aspekte der Kooperation)

NFDI4Culture - Consortium for research data on material and immaterial cultural heritage - Altenhöner, Reinhard; Blümel, Ina; Boehm, Franziska; Bove, Jens; Bicher, Katrin; Bracht, Christian; Brand, Ortrun; Dieckmann, Lisa; Effinger, Maria; Hagener, Malte; Hammes, Andrea; Heller, Lambert; et al. (Research Ideas and Outcomes)
Digital data on tangible and intangible cultural assets is an essential part of daily life, communication and experience. It has a lasting influence on the perception of cultural identity as well as on the interactions between research, the cultural economy and society. Throughout the last three decades, many cultural heritage institutions have contributed a wealth of digital representations of cultural assets (2D digital reproductions of paintings, sheet music, 3D digital models of sculptures, monuments, rooms, buildings), audio-visual data (music, film, stage performances), and procedural research data such as encoding and annotation formats. The long-term preservation and FAIR availability of research data from the cultural heritage domain is fundamentally important, not only for future academic success in the humanities but also for the cultural identity of individuals and society as a whole. Up to now, no coordinated effort for professional research data management on a national level exists in Germany. NFDI4Culture aims to fill this gap and create a user-centered, research-driven infrastructure that will cover a broad range of research domains from musicology, art history and architecture to performance, theatre, film, and media studies. The research landscape addressed by the consortium is characterized by strong institutional differentiation. Research units in the consortium's community of interest comprise university institutes, art colleges, academies, galleries, libraries, archives and museums. This diverse landscape is also characterized by an abundance of research objects, methodologies and a great potential for data-driven research. In a unique effort carried out by the applicant and co-applicants of this proposal and ten academic societies, this community is interconnected for the first time through a federated approach that is ideally suited to the needs of the participating researchers. To promote collaboration within the NFDI, to share knowledge and technology and to provide extensive support for its users have been the guiding principles of the consortium from the beginning and will be at the heart of all workflows and decision-making processes. Thanks to these principles, NFDI4Culture has gathered strong support ranging from individual researchers to high-level cultural heritage organizations such as the UNESCO, the International Council of Museums, the Open Knowledge Foundation and Wikimedia. On this basis, NFDI4Culture will take innovative measures that promote a cultural change towards a more reflective and sustainable handling of research data and at the same time boost qualification and professionalization in data-driven research in the domain of cultural heritage. This will create a long-lasting impact on science, cultural economy and society as a whole.
Keywords: Research Data Management